2006
DOI: 10.1073/pnas.0603715103
|View full text |Cite
|
Sign up to set email alerts
|

Migratory shearwaters integrate oceanic resources across the Pacific Ocean in an endless summer

Abstract: Electronic tracking tags have revolutionized our understanding of broad-scale movements and habitat use of highly mobile marine animals, but a large gap in our knowledge still remains for a wide range of small species. Here, we report the extraordinary transequatorial postbreeding migrations of a small seabird, the sooty shearwater, obtained with miniature archival tags that log data for estimating position, dive depth, and ambient temperature. Tracks (262 ؎ 23 days) reveal that shearwaters fly across the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
413
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(432 citation statements)
references
References 33 publications
15
413
4
Order By: Relevance
“…Spatiotemporal variation in wind strength and direction can shape not only the routes followed by birds, resulting in the well-known 'figure-of-eight' path of some transequatorial migrants (e.g. Shaffer et al 2006;González-Solís et al 2007), but also the timings of migration (Felicísimo et al 2008). This dependence on wind conditions is closely related to the type of flight adopted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spatiotemporal variation in wind strength and direction can shape not only the routes followed by birds, resulting in the well-known 'figure-of-eight' path of some transequatorial migrants (e.g. Shaffer et al 2006;González-Solís et al 2007), but also the timings of migration (Felicísimo et al 2008). This dependence on wind conditions is closely related to the type of flight adopted.…”
mentioning
confidence: 99%
“…Shaffer et al 2006;González-Solís et al 2007;Guilford et al 2009;Dias et al 2012a). Like other pelagic migrants, shearwaters are often faithful to their wintering sites in successive years Raine et al 2013), but so far no studies have addressed their year-to-year fidelity in routes and stopovers.…”
mentioning
confidence: 99%
“…climate) that may have consequences for migratory behaviour and species survival [6]. It is therefore suggested that global migrators, such as transoceanic migratory birds, may be useful as biological indicators of climate and oceanic health [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are oft en limited to methods (for example, stable isotopes) that require indirect steps to link the breeding and non-breeding grounds of individual birds. Th e advent of small, lightweight geolocators allows these links to be made directly 12 , but the need to retrieve units to access data has limited their use to site-faithful species using accessible, high-density breeding sites 13,14 . Bar-tailed godwits breed cryptically in low densities across over 1,800 km of remote coastal tundra within Alaska 10 , making breeding studies extremely diffi cult.…”
mentioning
confidence: 99%